2004
DOI: 10.1063/1.1687034
|View full text |Cite
|
Sign up to set email alerts
|

Nitridation effects on Pb center structures at SiO2/Si(100) interfaces

Abstract: P b -type interface defects in (100) Si/SiO 2 structures grown in ozonated water solution

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 29 publications
0
3
1
Order By: Relevance
“…The main differences between the two defects are in the dangling bond axis of symmetry [12][13] and in differences in the defects' electronic density of states [14][15][16][17][18]. However, in contrast to the reports of Fujieda et al [8][9][10], we observed that NBTS generates a completely new defect center in PNO-based devices. Despite this fundamental atomic-scale difference in defect generation, the defect generation activation energies for both PNO and SiO 2 devices were found to be equivalent within experimental error.…”
Section: Introductioncontrasting
confidence: 78%
See 2 more Smart Citations
“…The main differences between the two defects are in the dangling bond axis of symmetry [12][13] and in differences in the defects' electronic density of states [14][15][16][17][18]. However, in contrast to the reports of Fujieda et al [8][9][10], we observed that NBTS generates a completely new defect center in PNO-based devices. Despite this fundamental atomic-scale difference in defect generation, the defect generation activation energies for both PNO and SiO 2 devices were found to be equivalent within experimental error.…”
Section: Introductioncontrasting
confidence: 78%
“…The conflicting high temperature anneal response might be a result of the fact that these E′ centers are confined within an ultrathin dielectric region. Fujieda et al reported that the addition of nitrogen in the gate dielectric caused a modification to the P b1 structure that lowered the g-value (g = 2.0027) for the magnetic field orientated parallel to the Si/dielectric normal [9][10]. Recall that the g is actually a second rank tensor quantity.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…From the fitting procedure with two lorentzian curves, g-values were determined to be 2.0058Ϯ 0.0006 and 2.0031Ϯ 0.0006, coincident well with values of P b0 -and P b1 -centers, respectively. 12 Their peak-to-peak width were 3.8 and 4.1 G, somewhat larger than reported values for the SiON/Si with 4.8% nitrogen content, 3.3 and 3.7 G. 12 This could be induced by high power microwave 13 and inevitable in SDT measurements. In order to reconfirm trap origins, we also measured the g-anisotropy map.…”
Section: Interface Traps Responsible For Negative Bias Temperature Inmentioning
confidence: 63%